An Unusual Case of Lower Extremity Clear Cell Hidradenocarcinoma - Marc Rafols; Odille Mejia; Kei Shing Oh; Blake Bendixen; Irving Jorge; Sumana Narayanan (Case Reports in Surgery)
Hidradenocarcinoma (HC) is a rare malignant sweat gland tumor with metastatic potential primarily located in the head, neck, and trunk. We present an unusual case of a large lower extremity Clear Cell HC managed with surgical resection and adjuvant locoregional radiation after excluding lymph node involvement.